PENERAPAN TOGAF UNTUK MENYUSUN MASTERP PLAN TEKNOLOGI INFORMASI PADA PERUSAHAAN HERBAL - Endang Sulistiyani; Herlinda Sandiarsi (MULTITEK INDONESIA, 2025)
The development of an Information Technology (IT) Master Plan plays a crucial role in aligning an organization’s business strategy with its IT strategy. However, previous studies indicate that many IT Master Plans remain limited to strategic planning without a clear implementation roadmap, leading to uncertainty and inefficiencies in IT resource utilization. The absence of a structured framework also hinders the in-depth identification of IT needs, resulting in suboptimal or outdated systems. This study aims to apply the TOGAF (The Open Group Architecture Framework) in the formulation of an IT Master Plan that includes a comprehensive roadmap. The research method involves analyzing business and IT requirements, designing enterprise architecture, and developing an implementation roadmap that outlines structured stages of digital transformation. The study produces an IT Master Plan for a herbal company, covering enterprise architecture and a roadmap for IT implementation from 2026 to 2030. A total of 12 key digital initiatives are proposed, with an estimated five-year implementation cost of Rp 36,500,000. These initiatives are designed to enhance operational efficiency, boost sales, and maintain alignment between internal capabilities and external dynamics within the herbal industry. The findings are significant in strengthening the digital readiness of herbal enterprises to face ongoing technological transformation challenges.